Avaliação de métodos de previsão de recalque a partir da transferência de carga de estacas escavadas em perfil de solo granular - Menezes, Pedro Henrique Lustosa Bezerra de (2018)
The deep foundation settlements could be predicted by several methods, which are mostly based on semi-empirical correlations in application restricted to the ground from where they were conceived. Therefore, it is necessary to innovate these methods and to design new methodologies to obtain predictions of more convergence with reality. A couple of the current methodologies use load transfer curves. In this sense, the present dissertation evaluates the accuracy of the predicted settlements for each of two piles size, one drilled and another auger cast. In order to evaluate the behavior of the drilled pile, two piles were used in the Experimental Field of Geotechnics and Foundations of the Federal University of Ceará (CEGEF - UFC), both with 1.5 m length and 0.1 m diameter. One of these piles was executed on top of a layer of expanded polystyrene to eliminate toe resistance. On the other hand, it was used a auger cast pile with 17 m long and 0.3 diameter, it was executed in physical education accommodation. The methods used in order to settlements pile predicting were: Aoki (1979, 1984), Bowles (2001), Cambefort Laws modified by Massad (1992), Poulos and Davis (1980) and Randolph and Wroth (1979) extended by Lee (1993). In addition, numerical simulations were used from computer programs: ALXPAXL, UniPile and RSPile. For the use of these methodologies, the adjacent subsoil to these piles was characterized from geotechnical tests. In the geotechnical characterization, it was used deformed patterns, it was taken at depths of 20 cm, 60 cm and 110 cm. And, to obtain resistance soil parameters, it was used triaxial compression test and direct shear test performed using undefined pattern taken at depths of 60 cm and 110 cm. The results were compared, in order to verify the convergence of the absolute values of settlements and the factor correlation with respect to the corresponding load test. The soil profile adjacent to the analyzed pile is classified as SM group and typical behavior of sand of low compactness. Based on the used methods, it was noticed a convergence in the predictions of the re settlements in the elastic zone. Finally, for the design load, the closest settlements prediction of the experimental value was obtained by using the method proposed by Massad (1992).